Case report: Francisella philomiragia bacteremia in a patient with acute lymphoblastic leukemia - Xi, Dee (Frontiers in Cellular and Infection Microbiology, 2023)
Francisella philomiragia is a Gram-negative coccobacillus, which is a very rare human opportunistic pathogen causing pneumonia and systemic infection. It is difficult to identify this bacterium through conventional Gram-staining and biochemical methods due to an amorphous Gram stain appearance after 24 h culture and its relatively fastidious and slow growth giving weak and/or delayed reactions in biochemical tests. It is often misidentified as other bacteria including Haemophilus spp., Pseudomonas aeruginosa, or Sphingomonas paucimobilis. False identification may delay the therapy of the patients and even endanger the patient’s life. Here, we report a case of a 34-year-old man with acute lymphoblastic leukemia infected by F. philomiragia, which was almost misdiagnosed. This case describes our identification of a patient with a systemic F. philomiragia infection. To our knowledge, this is the first such case reported in China.